Retrospective evaluation of hyperproteinorrachia without pleocytosis (albuminocytologic dissociation) and survival in dogs. (25th August 2021) - Draper, Alexandra C. E.; Marshall, Laura J. C.; Williams, Timothy L.; Archer, Joy; Alves, Lisa
Abstract: Background: Hyperproteinorrachia (raised cerebrospinal fluid total protein [CSF‐TP]) without pleocytosis (HP) (also known as albuminocytologic dissociation) is identified in dogs with different neurologic diseases. However, the association between survival and increased CSF‐TP is unknown. Objectives: (a) Identify conditions commonly associated with HP in dogs and (b) investigate whether higher CSF‐TP concentrations or other relevant factors are associated with 1‐year survival. Methods: This is a retrospective study that identified dogs with HP (Cisternal CSF‐TP >0.30 g/L, Lumbar CSF‐TP >0.45 g/L with total nucleated cell concentrations [TNCCs] and RBC counts within RIs) from 2008 to 2019: recording signalment, weight, vital parameters, inflammation, neuroanatomic localization, CSF‐TP, sampling site, final diagnosis, etiologic classification, and 1‐year survival. Corrected CSF‐TP was calculated as CSF‐TP minus 0.3 (cisternal) or 0.45 (lumbar or unknown). Descriptive statistics were produced, CSF‐TP differences between groups (eg, neuroanatomic localizations) were evaluated using the Mann‐Whitney U test or Kruskal‐Wallis test (post‐hoc testing). The Cox proportional hazards model was used for survival data. Statistical significance was set at a P  < 0.05. Results: In all, 39 dogs had HP, associated with 17 conditions, including neoplasia (n = 6), meningoencephalitis of unknown origin (n = 4) (MUO), and intervertebral disc disease (n = 4) (IVDD) as the most common conditions. There was no significant difference between the CSF‐TP/corrected CSF‐TP between 1‐year survivors and non‐survivors, nor was there a difference between different neuroanatomic localizations or etiologic classifications ( P  > 0.05). Neoplasia, after adjustment for age, was the only variable associated with a worse survival ( P  = 0.01 HR: 2.08 (95% CI: 1.65‐39.2). CSF‐TP was not associated with age ( P  > 0.05). Conclusions: HP in dogs is associated with a wide range of conditions; the most common conditions are neoplasia, MUO, and IVDD. Higher CSF‐TP levels do not correlate with a worse 1‐year survival; however, they do correlate with neoplastic lesions.